Food allergies and intolerances in patients with fibromyalgia: the state of the art - M. Di Stefano; C. Capittini (Verduci Editore, 2024)
The approach to adverse reactions to food represents a difficult task for clinicians due to several unmet needs encompassing all the phases of the medical act. Globally, the prevalence of these reactions shows a progressive increase, but it should be considered that the prevalence of food allergy is largely affected by the diagnostic test used; nonetheless, the lack of accurate tests makes it difficult to calculate the prevalence of food intolerance. In patients suffering from fibromyalgia, food intake is very frequently reported as one of the main responsible for worsening of symptoms, and at diagnosis many patients have already modified their diet, often without a previous nutritional evaluation. Patients frequently start a gluten-free diet and/or a lactose-free diet before the real need is ascertained. Dairy products, incompletely absorbed carbohydrates and gluten-containing foods represent the products the patients consider more frequently the culprit of the onset or worsening of their symptoms. However, the known nocebo effect of foods may induce patients to erroneously associate some foods to symptom onset, also causing a useless elimination diet. The strict association between fibromyalgia and functional gastrointestinal disorders increases the difficulty clinicians have to front during diagnostic approach. Further studies are needed to define the real prevalence of allergy and intolerance in fibromyalgia and to select foods with a negative or positive effect on symptoms.